Optimizing Parameters of AWJM for Ti-6Al-4 V Grade 5 Alloy Using Grey Entropy Weight Method: A Multivariable Approach - Dubey A.K.; Kumar Y.; Kumar S. (My University, 2025)
Abrasive water jet machining (AWJM) is a highly efficient modern machining processes that allows the processing of various materials without altering their properties. Ti-6Al-4 V grade 5 alloy are used in multiple applications, like aircraft engines, surgical instruments, and medical implants. The response surface methodology-Box–Behnken Design is inutile, encompassing three process parameters, each with three levels. The entire experimental plan, consisting of 15 distinct experiments, was meticulously designed using Design Expert v13 statistical analysis software. These parameters include Abrasive flow rate (Af), stand-off distance (Sd) and Nozzle traverse speed (Tv). The Grey entropy weight (GEW) approach enables the analysis of measured machining performances, such as material removal rate, surface roughness and kerf taper angle (θ). Nozzle traverse speed (Tv) has the least influence on performance while stand-off distance (Sd) has the highest. Experimental results demonstrated a substantial enhancement in Grey relational grade (GRG) using Grey entropy weight (GEW) method and the growth in GRG was measured at 0.27. This current research will furnish valuable insights to researchers and industries engaged in the field of AWJM. Therefore, by introducing novelty and innovation, this paper makes a significant and valuable addition to the relevant literature. © The Institution of Engineers (India) 2024.